Systematic Literature Review: The Role of the Health System in Combinating HIV/AIDS: Challenges and Effective Strategies - Putri, Karisma Yustica; Firda, Fathiyyatu Assadiy; Warhas, Vania Anandila Dewi; Ningtiyas, Devy Ayu; Putri, Kezya Maharani; Utami, Siti Holiza (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: HIV/AIDS is a global health issue with widespread impact, affecting not only individuals infected but also society and healthcare systems. Efforts to combat HIV/AIDS require active involvement from the healthcare system in prevention, diagnosis, treatment, and psychosocial support. The main challenges in these efforts include social stigma, limited access to healthcare services, and the continuous increase in the number of cases. Method: This study uses a literature review approach, analyzing journals and articles published between 2019 and 2024, sourced from databases such as PubMed, SageJournals, and SpringerLink. The analysis focuses on the role of the healthcare system in addressing HIV/AIDS, the challenges faced, and effective strategies to overcome these issues. Results: The study found that the biggest challenges in HIV/AIDS management include a lack of public awareness, low early detection rates, and limited resources at healthcare facilities. Effective strategies include public education, improving access to healthcare services, and strengthening referral systems. Conclusion: The healthcare system plays a crucial role in the fight against HIV/AIDS. Despite the significant challenges, the implementation of appropriate strategies, such as education, better access to healthcare services, and combating stigma, can improve the effectiveness of HIV/AIDS control programs.